The Properties of a Coal Body and Prediction of Compound Coal-Rock Dynamic Disasters - Guowei Dong; Xuanming Liang; Zhen Wang (Shock and Vibration)
Since the precise identification and prediction and early warning of compound coal-rock dynamic disaster remain difficult, a new coal characterisation and prediction method for compound coal-rock dynamic disasters was described based on theoretical analysis, laboratory experiment, field sampling, mathematical treatment, and industrial testing. The results implied that the physicomechanical properties of coal in a compound coal-rock dynamic disaster are between those pertinent to a typical rock burst and a coal-gas outburst, i.e., with high crustal stress surrounding pressure, high gas pressure, low permeability, bump proneness, and outburst risk. The predicted drilling data indicate moderate gas desorption indices. The gas desorption velocity and permeability of compound coal-rock dynamic disaster coal decrease with the increase in crustal stress, while increase and decrease with the increase in gas pressure, respectively, at the same time, and they change little with increasing temperature. Gas extraction leads to the increase in coal mass brittleness and bump proneness. Based on the unique physical-mechanical properties of compound coal-rock dynamic disaster coal, a reasonably sensitive predictive index and critical value for Donglin Coal Mine were determined.